Given the equation system:
![\begin{cases}3x=4y \\ 4x-5y=2\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/p7flhxiowy2zdgfv1nsi38aftpzck3tay1.png)
To solve this equation system using the elimination method, first, you have to express both equations using the standard form. This means you have to express the first equation to standard form, for this you have to equal the equation to zero:
![\begin{gathered} 3x=4y \\ 3x-4y=4y-4y \\ 3x-4y=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b0oezclwls03des1lkqancticr3xf8xzje.png)
Now you have to multiply both equations by a number so that the leading coefficients are the same.
The first coefficients of the s